Two Cases of Dedifferentiated Endometrioid Carcinoma: Case Presentation and Brief Review of the Literature - Sachiko Morioka; Yasuhito Tanase; Ryuji Kawaguchi; Tomoko Uchiyama; Hiroshi Kobayash (Hindawi Limited, 2018)
Endometrioid carcinoma is the most common histological type of uterine endometrial cancer and particularly dedifferentiated endometrioid carcinomas (DEC) are less commonly observed. Silva et al. reported the biological features of UC based on the undifferentiated component of DEC, although the component represented only 20% of undifferentiated carcinoma. In this study, we report two cases of DEC with different presentation. Case 2 presented with the invasion to the bladder, rectum, and LN metastases. In contrast, the tumor in case 1 advanced into the endometrial cavity, similar to an endometrial polyp, without myometrial invasion. Hence, the diagnosis was established early. While we strive to improve the diagnosis of DEC, it is also crucial to better assess the prognosis and the appropriate treatment for the patients with established diagnosis of DEC.